(untitled) (Experimental biology, 2023)
The experimental data on establishment of adventitious roots cultures of endemic species Allochrusa gypsophiloides (turkestan soaproot), a super-producer of triterpene saponins, are presented. The primary isolated roots culture was obtained from initial seeds collected from natural populations of A. gypsophiloides in the south of Kazakhstan. The influence of different types of exogenous auxins, NAA and IBA of MS nutrient liquid medium on the root explants growth, the growth index of induced adventitious roots, and their biosynthetic potential by the saponins accumulation in vitro was studied. The general dynamics of growth was established: an increase in root biomass on 40-50’s culture days with a further decrease during a two-month cycle. It was revealed that the auxin stimulating effect is associated with the initiation of root apexes in the induced callus tissue, leading to the development of adventitious roots and intensive growth of differentiated root biomass in an isolated culture. The excess of biomass accumulation in the experimental variants of the medium averaged 215% compared to the control medium with an earlier inducing effect of IBA. It was found that the level of saponins in the extracts obtained from the adventitious roots culture, exceeded their content in similar extracts from native roots: 2 times in the control medium, 3 times in the medium with NAA and IBA. Saponins level increasing in culture correlated with biomass growth index on medium supplemented with auxins. The high saponins content in the extracts from the residual growth medium indicates the active exudation of saponins from the root biomass into the nutrient medium. Biotechnological bases for obtaining in vitro culture of adventitious roots with a high growth index and an increased saponins level on inducing medium for alternative production of secondary metabolites from the cultivated biomass of turkestan soaproot A. gypsophiloides have been developed.